Unpacking the Concept of Otherness: Philosophical and Psychological Perspectives - Doubková, Nikola; Preiss, Marek; Sanders, Edel Marie (Integrative psychological & behavioral science, 2024)
Otherness is a complex and polysemic notion that is conceptualized in both philosophy and psychology. The paper examines otherness as a universal phenomenon of the human psyche that manifests in relation to oneself and interpersonal relationships with others. Philosophical ideas, including those of Hegel, Lévinas and Waldenfels, are introduced as providing essential theoretical background for psychological studies of otherness. The psychological section deals with otherness from various perspectives, with emphasis on internal processes of an individual, drawing on theories within psychoanalytical and intrapsychic traditions, as well as the intersection of otherness and identity. Otherness is introduced as a variable influencing complex individual and social processes, such as the perception of individuals and groups. Finally, a taxonomy of otherness is proposed that reflects the multifaceted nature of the concept and could help navigate the existing literature as well as guide new studies.
Keywords: Psychological Theory; Social Perception; sociální percepce; interpersonální vztahy; lidé; psychologická teorie; Interpersonal Relations; filozofie; Humans; Philosophy